THE GLOBAL COMPETITIVENESS OF THAILAND: AN EMPIRICAL ANALYSIS OF THE ASEAN COMMUNITY - John, Varughese K; Duangekanog, Duangta; Wichayachakorn, Asawin; Vikitset, Nithiphong (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
The current rate of technological expansion and the globalization of markets have made countries to be more competitive for their economic growth and prosperity. The Global Competitiveness Index (GCI) is a measure computed by the World Economic Forum every year since 1979 on the basis of 12 pillars of economic and human growth indicators. 138 world countries are included in the GCI 2016-17 and these countries account for 98% of the world GDP. Thailand is the third major economy among the ASEAN community and it is classified as ‘Efficiency Driven Economy’ according to its score in GCI 2016-17. This study investigates the factors in which Thailand has greater strength and more weakness when compared with the other ASEAN countries based on the GCI indicators. Accordingly, Thailand seems to be comparatively weak in Innovation and Institutional factors but strong in Macroeconomic environment factors, Health and Primary Education measures, and Market Size. The study concludes that if the economic and human development policies are formulated looking into these strengths and weaknesses, the country can become an ‘Innovation-driven economy’ within a short span of time.